1992
DOI: 10.3758/bf03206766
|View full text |Cite
|
Sign up to set email alerts
|

Auditory apparent motion in the free field: The effects of stimulus duration and separation

Abstract: The effects of stimulus duration and spatial separation on the illusion of apparent motion in the auditory modality were examined. Two narrow-band noise sources (40 dB, A-weighted) were presented through speakers separated in space by 2.5°, 5°, or 10°, centered about the subject's midline. The duration of each stimulus was 5, 10, or 50 msec. On each trial, the sound pair was temporally separated by 1 of 10 interstimulus onset intervals aSOIs): 0, 2, 4, 6, 8, 10, 15, 20, 50, or 70 msee. Five subjects were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 6 publications
3
20
1
Order By: Relevance
“…AAM can be heard at the same burst duration-SOA combinations for separations between 3°and 160°, under monaural and binaurallistening conditions and for sources separated in the horizontal and midsaggital planes (Strybel, Manligas, Chan, & Perrott, 1990;Strybel & Neale, 1994;Strybel, Witty, & Perrott, 1992). In fact, motion can be heard when the lead and lag stimulus are presented from a single loudspeaker (Strybel, 1994;Perrott & Strybel, 1997).…”
Section: Auditory Velocity Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAM can be heard at the same burst duration-SOA combinations for separations between 3°and 160°, under monaural and binaurallistening conditions and for sources separated in the horizontal and midsaggital planes (Strybel, Manligas, Chan, & Perrott, 1990;Strybel & Neale, 1994;Strybel, Witty, & Perrott, 1992). In fact, motion can be heard when the lead and lag stimulus are presented from a single loudspeaker (Strybel, 1994;Perrott & Strybel, 1997).…”
Section: Auditory Velocity Perceptionmentioning
confidence: 99%
“…The detection of AAM is affected by burst duration and SOA, however. The minimum burst duration for the illusion is roughly 25 msec (Strybel & Neale, 1994;Strybel et al 1992), and the SOAs that produce AAM increase with burst duration, according to Korte's second law ofvisual apparent motion (Briggs & Perrott, 1972;Strybel & Neale, 1994). Although only stimulus timing affects the minimum conditions for motion, both spatial and temporal factors affect discrimination ofthe direction ofmotion.…”
Section: Auditory Velocity Perceptionmentioning
confidence: 99%
“…Whether the listener can perceive the discrete motion as continuous or not is dependent on conditions such as the spatial separation of sounds, stimulus duration, moving velocity, or time-step (time period of the discrete motion) of the discrete process. Strybel et al [8] investigated the effects of stimulus duration and spatial separation of two sounds that were displayed through two loudspeakers in a free field alternately. Lakatos [9] also reported that their results indicated a direct 2 Advances in Acoustics and Vibration relationship between the horizontal separation of two sounds and the critical stimulus onset asynchrony (SOA).…”
Section: Introductionmentioning
confidence: 99%
“…The range of burst duration and the ISOI for auditory apparent motion is not sensitive to the location and the spatial interval of stimuli (Nakajima et al, 1990 ;Strybel et al, 1990 ;Strybel et al, 1992 ;Strybel 1993 ;Mizushima et al, 1994), unlike that for visual apparent motion (Korte, 1915 ;Scholz, 1924 ;etc.). The timing condition for auditory continuous motion is also independent of whether monaural listening or binaural listening is used (Strybel and Neale, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the relationship between the burst duration and the ISOI, Briggs and Perrott (1972) classified the perception under dichotic listening into five categories : single sound, simultaneous sounds, continuous motion, broken motion, and successive sounds. Strybel et al (1989Strybel et al ( , 1990Strybel et al ( and 1992) also investigated the relationship between the category and the timing under binaural and monaural conditions in a free field. They replicated the results obtained by Briggs and Perrott (1972).…”
Section: Introductionmentioning
confidence: 99%